LANGUAGE RESEARCH METHODOLOGIES: A SYSTEMATIC REVIEW AND EMPIRICAL SURVEY ON STUDENTS' INTRODUCTORY UNDERSTANDING OF RESEARCH METHODS - Bahagia Saragih; Ayrine Nazarany Saragih; Malika Assyifa; Widya Praninda Hasibuan; Afiyah Syafina; Raisyah Shalsabila; Icen Mekartini Napitupulu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines major methodological approaches in language research and simultaneously investigates the foundational research-related awareness of junior secondary school students as an educational reference point. A systematic literature review was carried out by synthesizing academic books, peer-reviewed journals, and scholarly sources covering seven methodological traditions: descriptive qualitative, descriptive quantitative, experimental, historical, comparative, etymological, and grounded theory. To situate these academic frameworks within an educational context, a small-scale descriptive survey involving 31 students from SMP Negeri 3 Tebing Tinggi, Sumatera Utara, Indonesia, was administered on May 7, 2026. The survey instrument was explicitly calibrated to the junior secondary school curriculum level; it probed students' general familiarity with introductory research concepts rather than their command of advanced paradigms. Findings from the literature review confirm that methodological selection must be driven by the nature of the research question and the characteristics of the data. Survey findings indicate that students hold a basic awareness of research-related activities drawn from their schoolwork experience, yet report limited confidence in formal research design and analytical terminology. The study concludes that progressive, age-appropriate methodological instruction is essential for cultivating long-term research literacy.